Luminophores in the fur of seven Australian Wet Tropics mammals - Linda M. Reinhold; Tasmin L. Rymer; David T. Wilson (PLoS ONE, 2025)
Bright photoluminescence in the fur of mammals has recently raised considerable scientific interest. The fur of many mammal species, including Australian northern long-nosed (Perameles pallescens) and northern brown (Isoodon macrourus) bandicoots, photoluminesces strongly, displaying pink, yellow, blue and/or white colours. We used reversed-phase high-performance liquid chromatography and electrospray ionisation mass spectrometry to investigate the luminophores contributing to this photoluminescence. At least two classes of luminophore were observed in bandicoot fur extracts, and four of the orange-pink photoluminescent molecules had molecular masses consistent with protoporphyrin, coproporphyrin, uroporphyrin and heptacarboxylporphyrin isomers. Fur extracts of three other species of marsupial, a placental and a monotreme also contained a luminophore consistent with the molecular mass of protoporphyrin, whether or not pink photoluminescence was evident in the pelage as a whole. This study is the first chemical analysis of luminophores contributing to photoluminescence in the fur of Australasian mammals since two tryptophan metabolites were identified more than 50 years ago.